The Use of Solar Panels as an Alternative Energy the Performance of DC Water Pumps for Agriculture - Nugroho, Adhadi; Baswara, Ahmad Raditya Cahya (Signal and Image Processing Letters, 2022)
This study designs a system that is used to spray mushroom plants automatically with a timer module. The work of the tool starts when the solar panel produces electrical energy whose voltage and current are controlled by the controller during the battery charging process from 07-00 to 17.00. When the load is used for a certain period of time, the digital timer module will signal the relay to supply electric current to the water pump load and cut back the electric current to the water pump. The PLTS system is designed so that it can be used to help watering mushroom farmers regularly every day. Based on the testing of the tools that have been carried out, data obtained that charging the battery using solar panels takes about 5-7 hours. in sunny conditions. In sunny conditions the highest light intensity of 7450 lux can produce 4.01 watts of power, 13.25 V voltage, and 0.30 A current. The duration of watering time is 1 minute using a DC water pump and requires 1 liter of water and an input current of 1.72 A. This study designed a system used to spray fungal plants automatically with a timer module. The work of the tool begins when the solar panel produces electrical energy whose voltage and current are controlled by the controller during the battery charging process from 07-00 to 17.00 hours. When the load is used at a certain time span the digital timer module will give a signal to the relay to flow electric current to the water pump load and cut off the electric current back to the water pump. The solar power plant system is designed to be used to help localize mushroom growers regularly every day. Based on the testing of the tool that has been carried out, data were obtained that the charging of the battery using solar panels is about 5-7 hours. in sunny conditions. In bright conditions the highest light intensity of 7450 lux can produce 4.01 watts of power, a voltage of 13.25 V, and a current of 0.30 A. Watering time duration is 1 minute using a DC water pump and requires 1 liter of water and an input current of 1.72 A.